Hidrostratigrafi Akuifer sebagai Geoindikator Genesis Bentuk Lahan di Wilayah Kepesisiran Kabupaten Kulonprogo, Daerah Istimewa Yogyakarta - Langgeng Wahyu Santosa (Universitas Muhammadiyah Surakarta, 2012)
Purpose of this research is to study on aquifer hydrostratigraphy that can be a geo-indicator of geomorphological processes on the past, that describe of landform genetic in the research area. The research method is survey. The framework of analysis in this research is landform genetic. The results of the research indicate that: (1)